Country Profiles, Indonesia - Population Council, New York, NY.; Population Council, New York, NY. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1971)
A profile of Indonesia is sketched in this paper. Emphasis is placed on the nature, scope, and accomplishments of population activities in the country. Topics and sub-topics include: location and description of the country; population - size, growth patterns, age structure, urban/rural distribution, ethnic and religious composition, migration, literacy, economic status, future trends; population growth and social and economic development - relationship to national income, relationship to size of the labor force, relationship to agriculture, relationship to social welfare expenditures; population policies - direct, indirect, relevant laws; history of population concerns; population programs - objectives, organization, operations, research and evaluation; and assistance from international agencies. Summary statements indicate that the family planning movement is in a transitional phase from a restricted volunteer program to one with significant governmental support. Cooperation of related population/family planning agencies is occurring and pilot projects and program plans have been initiated for a national five-year program of family planning services. A map of the country is drawn. (BL)
Availability: The Population Council, 245 Park Avenue, New York, New York 10017 (Free).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Biographies; Demography; Developing Nations; Family Planning; National Programs; Population Distribution; Population Growth; Population Trends; Social Sciences